2010
DOI: 10.1007/s11745-010-3415-2
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acid Composition of the Maternal Diet During the First or the Second Half of Gestation Influences the Fatty Acid Composition of Sows' Milk and Plasma, and Plasma of Their Piglets

Abstract: Dietary supplements of olive oil (OO) or fish oil (FO) during the first (G1: day 1-60) or second half of gestation (G2: day 60 to term, day 115) were offered to pregnant sows. The proportion of fatty acids in milk and plasma were determined by gas chromatography. When supplements were given during G1, the proportions of oleic acid (OA) and arachidonic acid (AA) in the plasma were higher in the OO group than in the FO group, whereas docosahexaenoic acid (DHA) was higher in the latter group at day 56 of gestatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 61 publications
3
19
0
1
Order By: Relevance
“…The endogenously low levels of RBC DHA at baseline may be explained in part by the negligible levels of DHA in the sow milk (0.01 ± 0.01% total FA), as were previously determined for this sow herd (Tyburczy et al, 2010a; Tyburczy et al, 2010b). The content of RBC DHA on days 14 and 21 is consistent with most (Amusquivar et al, 2010; Blanaru et al, 2004; Mathews et al, 2002; Mollard et al, 2005), but not all (Huang et al, 2007) studies of rapidly-growing, neonatal pigs with comparable DHA intakes, but is lower than the RBC DHA levels of human infants (Hoffman et al, 2008; Hoffman et al, 2006; Miller et al, 2010; Minns et al, 2010). …”
Section: Discussionsupporting
confidence: 79%
“…The endogenously low levels of RBC DHA at baseline may be explained in part by the negligible levels of DHA in the sow milk (0.01 ± 0.01% total FA), as were previously determined for this sow herd (Tyburczy et al, 2010a; Tyburczy et al, 2010b). The content of RBC DHA on days 14 and 21 is consistent with most (Amusquivar et al, 2010; Blanaru et al, 2004; Mathews et al, 2002; Mollard et al, 2005), but not all (Huang et al, 2007) studies of rapidly-growing, neonatal pigs with comparable DHA intakes, but is lower than the RBC DHA levels of human infants (Hoffman et al, 2008; Hoffman et al, 2006; Miller et al, 2010; Minns et al, 2010). …”
Section: Discussionsupporting
confidence: 79%
“…The essential role of lipids during the perinatal period has received more attention in the last decades [12,27,[32][33][34][35][36]. Postnatal fatty acid availability in the neonate depends on fatty acid content of milk, and milk fatty acid profile has been found to be related with maternal diet [36][37][38][39]. In the present study we focused on the effects of maternal supplementation with different fat sources (olive oil, butter and margarine which are used widely in the Western diet) on fatty acid milk composition and on the possible impact of these fat sources on offspring weight gain and fat accumulation during the suckling period.…”
Section: Discussionmentioning
confidence: 99%
“…This confirms that either DHA is taken up through the placenta into the embryo during early pregnancy or that more EPA was taken up by the embryo and then converted to DHA. As tissues of pigs from n-3 LCPUFA supplemented sows also showed higher EPA and DHA levels at birth than pigs from Control sows (Rooke et al, 2001b and2001c), it is likely that n-3 LCPUFA uptake continues throughout gestation, although Amusquivar et al (2010) showed that n-3 LCPUFA levels were increased in sow milk and pig plasma when sows were only supplemented with n-3 LCPUFA during the first half of gestation (days 1 to 60), suggesting that n-3 LCPUFAs can be stored in maternal adipose tissue and mobilized during milk production. When sows were supplemented with n-3 LCPUFAs in gestation and lactation, n-3 LCPUFA levels were also higher in colostrum and milk (Taugbol et al, 1993;Rooke et al, 2000 and2001a).…”
Section: Discussionmentioning
confidence: 99%